Nocardia Subretinal Abscess: A Rare and Challenging Case Report - Ana Maria Cunha; Marta Silva; Ana Catarina Pedrosa; Fernando Falcão-Reis; Luís Figueira (Case Reports in Ophthalmological Medicine)
Purpose. To describe a positive clinical response of a patient with submacular Nocardia abscess due to a rapid and efficient treatment. Case report. We describe a case of a 50-year-old man with a painless visual decline of the left eye. Four years later, he had been diagnosed with systemic nocardiosis. Examination of the left eye revealed a submacular white mass with fluffy borders and another smaller white lesion, with well-defined borders, in the inferior temporal vascular arch. A systemic antibiotic treatment with SMX-TMP and intravenous imipenem and a single intravitreal injection of bevacizumab was performed. Conclusion. Prompt diagnosis and treatment ensured an expeditious resolution of the abscess and significant improvement of visual acuity. The diagnostic approach of a high index of suspicion coupled with directed treatment is required when dealing with subretinal inflammatory lesions.